Broad bandgap tuning and emission interplay between silicon quantum dots and defect states in RF-sputtered silicon oxynitride thin films - Garrido-García, Luis Fernando; Pérez-Martínez, Ana Laura; López-Suárez, Alejandra; Aguilar-Del-Valle, María del Pilar; Rodríguez-Gómez, Arturo (Frontiers in Physics, 2026)
Silicon oxynitride (SiON) thin films were grown by RF magnetron sputtering system (RF-MS) from both pure and silicon-enriched Si3N4 targets, enabling systematic exploration of substrate temperature, RF power, and target composition. The resulting materials diverge from conventional stoichiometric SiON, forming silicon-rich, non-stoichiometric films whose optical and structural responses are strongly parameter-dependent. The effective optical bandgap was tuned across 2.17–3.09 eV, driven by the interplay of oxygen incorporation, defect states, and the emergence of embedded Si nanoclusters. The refractive index spanned 1.41–2.11, mapping a broad compositional continuum across the studied deposition conditions. Microstructural analyses by SEM, TEM, and diffraction revealed that silicon inserts promote localized crystallinity and the formation of quantum-dot-like domains. These features correlate with a sharp photoluminescence peak at 3.24 eV. Surface characterization by AFM showed that roughness is critically governed by RF power and temperature, with silicon inserts further amplifying nanoscale disorder. Film thickness scaled with power and time, exceeding 2 µm under high-power, high-temperature, insert-modified conditions. Together, these results demonstrate that careful tuning of sputtering parameters provides access to non-stoichiometric SiON thin films with controllable bandgap, refractive index, and microstructure, making them particularly promising for planar optical waveguide integration, near-UV/blue light-emitting layers, and (complementary metal–oxide–semiconductor) CMOS-compatible photonic and sensing platforms.